(untitled) (Bangladesh Journal of Medical Education, 2017)
This cross sectional descriptive study was conducted to observe the quality of Pharmacology professional written question papers of Bangladesh University of Professionals (BUP), University of Chittagong (CU), University of Dhaka (DU), Rajshahi University (RU) and Shahjalal University of Science & Technology (SUST). For this purpose total 82 SAQ papers of five universities dated from January 2007 to July 2015 were reviewed. Question papers were reviewed to find out the coverage of recall, understanding and problem solving type questions, content coverage and presence of marking scheme in SAQ papers. Mean percentage of recall, understanding and problem questions were 54.3%, 44% and 01.7% respectively in SAQ papers. Mean of the recall questions of SUST statistically significantly differed from curriculum standard 60%. Other universities had no significant differences with the standard. Mean of the understanding questions of all the universities statistically significantly differed from curriculum standard 30% except BUP. There was statistically significant difference between mean of the problem solving questions of all the universities and curriculum standard 10% . Most of the SAQ papers (62%) were without problem based questions. No question paper was found having different types question as per curriculum standard. Total 15(18.3%) SAQ papers contained 100 % topics (all the 11 groups). Thirty nine (47.6) contained 10 groups and 22% contained 9 groups out of 11. Twelve percent SAQ papers contained less 80% topics Total 29 (35.4%) SAQ papers of all the universities showed marking scheme on the questions papers, rest 64.6% were devoid of it. Maximum 87.5% SAQ papers of RU had marking scheme. Findings of this study may be used to redefine the distribution of different types question in SAQ papers and to improve the quality of question papers by ensuring their coverage. Bangladesh Journal of Medical Education Vol.8(2) 2017: 12-17